Význam imunitního systému a možnosti imunoterapie u maligního melanomu - Krajsová, I (Klinicka onkologie, 2015)
Over the past several years, many important changes in the treatment of metastatic melanoma have occurred. New treatment options have been discovered to exploit inhibition of immune checkpoints for promotion of antitumor immune response. Recent results of clinical studies with anti-CTLA 4 and anti-PD 1 monoclonal antibodies show the ability of immunotherapy to extend progression free survival and overall survival in patients with metastatic melanoma when compared to chemotherapy and other therapeutic methods. This article focuses on efficacy and safety of these immunotherapeutic approaches and considered biomarkers of tumor response.
Keywords: Melanoma; melanom; Antibodies, Monoclonal; Humans; Programmed Cell Death 1 Receptor; monoklonální protilátky; antigeny CD279; CTLA-4 Antigen; lidé; antigen CTLA-4